Lo. Ṭiḷakāñce Kesarīntīla lekha - Tilak, Bal Gangadhar, 1856-1920 (SAMP early 20th-century Indian books project, 1922)
Collection of articles on the political situation in colonial India; previously published in Kesari, Marathi weekly.